Criminology - Case, Stephen; Johnson, Philip (Lecturer in criminology); Manlow, David; Smith, Roger S. (Roger Shipley), 1953-; Williams, Katherine S. (Oxford : Oxford University Press, 2017)
'Criminology' is a core, introductory textbook that takes students further. From the first chapter, students are encouraged to regard themselves as producers of criminological knowledge. Starting from the basics, the book takes students on a journey through the subject. This begins with what crime is and the theories that try to explain it, through society's response to crime, and ultimately to how to carry out independent research and plan first steps in a career. The critical, applied approach is emphasized through some of the many features that are integrated throughout the book. These include conversations with authentic voices from the field, compelling personal insights from the authors, and challenges to students to question assumptions, apply knowledge and critically reflect on their personal viewpoints.
Includes bibliographical references (pages 879-908) and index.
Keywords: Criminology